2019
DOI: 10.1002/admt.201900106
|View full text |Cite
|
Sign up to set email alerts
|

A Dual‐Gate InGaZnO4‐Based Thin‐Film Transistor for High‐Sensitivity UV Detection

Abstract: produces some real risks, including wrinkles, pigmented flat spots known as liver spots, and even skin cancer. [1][2][3][4] These are mostly attributed to the effects of UV light, a shorter wavelength than the visual spectrum. Therefore, over the past decades, developments in UV sensors have received significant attention for their potential positive effects on human health.When considering the performance of many different UV sensors, required features include high sensitivity, stability, and linearity. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…AOS film is usually prepared by magnetic sputtering or the solution‐processing method. [ 5–7 ] AOS films prepared by the sputtering technique have good uniformity, reproducibility, productivity but relatively high fabrication cost. In comparison, the solution‐processing technique is with the merits of low cost, large‐area compatibility, and potential low‐processing temperature on low‐cost flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
“…AOS film is usually prepared by magnetic sputtering or the solution‐processing method. [ 5–7 ] AOS films prepared by the sputtering technique have good uniformity, reproducibility, productivity but relatively high fabrication cost. In comparison, the solution‐processing technique is with the merits of low cost, large‐area compatibility, and potential low‐processing temperature on low‐cost flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Research focus in this direction is necessary as the graphene/ ZnO nanostructures provide better device performance by bringing in synergistic effects in electron transport as well as light absorption. Even though transistors are a compelling option towards development of UV detectors, they require complex fabrication processes and patterning for techniques to achieve required resolutions [15][16][17]. The advantage of using diode-based detector is that larger areas can be made available for UV detection, the sensitive area in a transistor-based sensor will be the channel or patterned gate which will have dimensions in the submicron range.…”
Section: Introductionmentioning
confidence: 99%
“…Next, in order to mimic the visual perception functionality of the human vision system, an IGZO 4 -based UV sensor was fabricated. Figure a displays a schematic illustration of the UV sensor with a structure of Ta/IGZO 4 /Pt, where a beam of UV light was illuminated vertically on the device, and its photoresponse properties were investigated. The detailed parameters can be found in the experiment part.…”
mentioning
confidence: 99%
“…Figure c illustrates the resistance state of the UV sensor in a dark environment and under UV illuminations with different wavelengths, including 365 nm, 254 nm, and simultaneous illuminations of both 365 and 254 nm. It can be clearly observed that the device resistance decreases as the wavelength decreases, which can be attributed to the interband transition and band-tail absorption of IGZO 4 films occurring in different light regions. It should be noted that, instead of using light pulses, here we investigated the light-sensing performance of the device under a persistent light illumination, and electrical pulses were used to read out the device state, showing that the conductance of the Ta/IGZO 4 /Pt devices is indeed a function of the input UV light. Hence, the IGZO 4 -based UV sensor can be used as a receiver of UV signals for sensing and information communication.…”
mentioning
confidence: 99%